ANTHROPOMETRIC AND ENDURANCE ADAPTATIONS FOLLOWING A FOUR-WEEK MICRO-EXERCISE REGIME AMONG MEDICAL STUDENTS - Mohammad Alif Iskandar, Jusnizan; Puteri Varissa Dania, Azlan Rosmera; Nor Syahidah, Baharuddin; Preveena, Baskaran; Norhida, Ramli; Marlynna, Sarkawi (2025)
Introduction: Micro-exercise, which involves short bursts of high-intensity activity, is emerging as a practical and time-efficient strategy to promote physical health, particularly in populations with limited time, such as medical students. Despite its potential, limited data exist on its effects on anthropometric outcomes and physical endurance among the medical students population. This study aimed to assess the impact of a structured micro-exercise intervention on selected anthropometric and physical endurance parameters. Methods: A total of 48 preclinical medical students were randomly assigned to control and intervention groups. The intervention group engaged in micro-exercise sessions four times per week. Anthropometric measurements (waist and hip circumference, body weight), muscular endurance (push-ups count), and cardiovascular recovery (pulse rate post-step test), were recorded pre- and post-intervention. Non-parametric tests (Wilcoxon Signed-Rank and Mann–Whitney U) were used due to non-normal data distribution. Results: Significant within-group improvements were found in the intervention group for hip circumference (p = 0.002), push-up performance (p = 0.001), and pulse rate post-exercise (p = 0.022). Between-group comparisons showed significant improvements in hip circumference (p = 0.011) and push-ups (p = 0.047). No significant changes in body weight were observed. Conclusion: A four-week micro-exercise regimen resulted in measurable improvements in anthropometric indicators and physical endurance among medical students. These findings suggest micro-exercise as a promising tool for improving musculoskeletal and cardiovascular health. Extended duration and larger samples are recommended for future studies. Keywords: Micro-exercise, physical endurance, anthropometric outcomes, medical students